"Romeo and Juliet" by Peter Tchaikovsky. The 400th anniversary of William Shakespeare’s death - Grajewski, Czesław (Saeculum Christianum. Pismo Historyczne, 2021)
With the biography of P. Tchaikovsky in the background, the author describes the circumstances of the creation of the overture Romeo and Juliet. Then he briefly analyses the composition itself and describes its character.